Does Cancel Culture call into Question the Protection of Artists' Rights of Expression? A Study in the Light of the Case-law of the European Court of Human Rights - Rosa Manzo (Athena, 2023)
Cancel culture calls into question the relation between artistic productions and values which these productions revoke. While it is widely accepted that art should not bear any constraints which might lead to censorship, it is open the discussion whether art works from the past should be removed or amended in light to the current democratic values endorsed by the western community.  This leads to a set of questions: will old art crafts find a place in our museums even if they depict scene of colonization or slavery openly in contrast with the democratic values and the modern concept of statehood?  To what extend the artistic freedom should be taken into account when it comes to historical art manufactories which remind old-fashioned values? The paper is structured as it follows: the first section will give an overview of the cancel culture movement, its genesis and its more recent developments. A second section will focus on the protection of artistic freedom of expression and its current state of art in the context of International and European law. The third section will discuss the jurisprudence of the European Court of Human Rights concerning artistic freedom of expression, with particular regards to the concept of European Literature Heritage. The last section will conclude.